Relationship Between Entrepreneurship Education Curriculum and Agricultural Students’ Satisfaction in China - Huang, Yangjie; Bu, Yajing; Liu, Lanying; Xu, Da; Xu, Zengliu; Zhao, Guojing (Frontiers in Psychology, 2022)
Developing agriculture is an important way to get rid of poverty and boost economic development. Entrepreneurship, especially entrepreneurship education, is considered to be an important contributor to the realization of the above objectives. Entrepreneurship education has received more and more attention. Improving the entrepreneurial willingness and skills of agricultural students is of great significance to the economic and social development of developing countries. In order to explore the relationship between entrepreneurship education curricula and satisfaction, especially the agricultural students, we conducted a questionnaire survey in 35 universities across the country between 2018 and 2019 to evaluate the entrepreneurship education of agricultural students in Chinese universities. And 1223 valid questionnaires with 7 interviews were obtained. Furthermore, we used the structural equation model to empirically analyze the questionnaire data and found that entrepreneurship practice plays a part in the mediating effect between entrepreneurship curriculum and satisfaction with entrepreneurship education. This paper expands literature on entrepreneurship education and has certain reference significance for training a large number of agricultural entrepreneurial talents the practice of entrepreneurship education in other developing countries.